Studies on interaction of green silver nanoparticles with whole bacteria by surface characterization techniques - Ferreyra Maillard, Anike Paula Virginia (2019)
The use of silver nanoparticles (AgNPs) with their novel and distinct physical, chemical, and biological properties, has proven to be an alternative for the development of new antibacterial agents. In particular, the possibility to generate AgNPs coated with novel capping agents, such as phytomolecules obtained via a green synthesis (G-AgNPs), is attracting great attention in scientific research. Recently, we showed that membrane interactions seem to be involved in the antibacterial activity of AgNPs obtained via a green chemical synthesis using the aqueous leaf extract of chicory (Cichorium intybus L.). Furthermore, we observed that these G-AgNPs exhibited higher antibacterial activity than those obtained by chemical synthesis. In order to achieve the green AgNPs mode of action as well as their cellular target, we aimed to study the antibacterial activity of this novel green AgNPs against Gram-negative (Escherichia coli) and Gram-positive (Staphylococcus aureus) bacteria. The effect of the G-AgNPs on the bacterial surface was first evaluated by zeta potential measurements and correlated with direct plate count agar method. Afterwards, atomic force microscopy was applied to directly unravel the effects of these G-AgNPs on bacterial envelopes. Overall, the data obtained in this study seems correlate with a multi-step mechanism by which G-AgNPs-lipid membrane interactions is the first step prior to membrane disruption, resulting in antibacterial activity.